From listening to curating: Anthropological curatorship toward music playlist practices - Ahnaf, Fikra (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2023)
Currently, the curatorial approach is expanding its influence beyond the limitations of museums and art galleries, transforming the experiences and significance of our daily existence. That is embodied, for example, in the curatorial practices of music playlists. In making a music playlist there must be a sound curation process where the songs to listen to are selected and included in the music playlist. Accordingly, this study aims to describe how users of analog (mixtapes) and digital (Spotify playlist) music playlists conduct their music curation process and perceive the relationships behind them. The curation process is analyzed using curatorial and anthropological frameworks, which also attempt to provide a fascinating background on preference formation and the curation process. Qualitative data was collected from a virtual ethnographic approach, with observations and unstructured-semi-structured interviews—offline and online—of 19 informants aged 21–55 living in Yogyakarta and Bandung and a literature review. The data obtained through this study focuses on two outcomes. First, sociocultural circumstances provide the basis for preference formation in selecting, curating, and making music playlists. Second, the particulars of each user's music playlist are related to self-discovery and individual identity. As a result, sociocultural circumstances persuade music playlist users' habits that attach to the curation process.